THE ROLE OF PATHOGENIC MICROORGANISMS IN THE ACCUMULATION OF BIOGENIC MAGNETIC NANOPARTICLES IN LUNG TISSUES - Gorobets, Svitlana; Gorobets, Oksana; Medviediev, Oleksandr; Kuzminykh, Liubov (Proceedings of National Aviation University (archive), 2017)
Purpose: In this paper the role of pathogenic microorganisms in the accumulation of biogenic magnetic nanoparticles in lung tissues is examined. The main purpose of the present research is to prove that biogenic magnetic nanoparticles can be accumulated in lung tissues because of the pathogenic microorganisms during lung disease. Methods: Pairwise and multiple alignment of amino acid sequences, electron paramagnetic resonance. Results: The producers of biogenic magnetic nanoparticles were found among pathogenic microorganisms that cause lung disease. Biogenic magnetic nanoparticles can be accumulated in lung tissues because of these pathogenic microorganisms during relevant lung diseases. The presence of biogenic magnetic nanoparticles in lung tissues was proved using the electron paramagnetic resonance spectra analysis. Discussion: The results of the present research can be used to understand the possible reasons of toxic and allergic effects and even corking of vessels during uncontrolled accumulation of magnetic nanoparticles in different organs and tissues because of their magnetic dipole-dipole interaction with biogenic magnetic nanoparticles on cell membranes and to prevent it.